Development Of Picture Card Media Based On Science Literacy On Ecosystem Materials - Aryandari, Mita; Sari, Prima Mutia (JIV-Jurnal Ilmiah Visi, 2024)
It is known that the science literacy score in Indonesia in PISA (Programe for International Student Assement) which is carried out in 2022 is up 6 positions compared to 2018. However, the score dropped by 13 points. This needs to be improved the quality of education in Indonesia, one of the factors that influence it is the lack of innovation in the use of science literacy-based learning media. The purpose of this study was to determine the characteristics, feasibility, and response to picture card media based on science literacy in grade V elementary school ecosystem materials. The research method used is R&D with the ADDIE model, namely analysis, design, development, implementation, and evaluation. To determine the feasibility of the media, a validation test was carried out by material experts and media experts using validation sheets. From the expert validation test, the material obtained a percentage of 100% with a very decent category. The results of the media test obtained a percentage of 100% with a very decent category. To determine the media response, respondents were filled out questionnaires by teachers and students. The results of students’ responses to the media obtained a percentage of 93% in the very good category. While the results of the teacher’s response obtained a percentage of 95% with a very good category. This study found that the picture card media based on science literacy ecosystem material is very feasible and very good to be used as a learning medium that can be an idea and motivation for teachers to make learning media innovations. In addition, it can help students in the learning process and increase knowledge related to science literacy skills. Further research can develop picture card media with other subjects and materials.